Novel resorbable bone wax containing β-TCP and starch microspheres for accelerating bone hemostasis and promoting regeneration - Duan, Qiangqiang; Liu, Huiling; Zheng, Lixia; Cai, Daozhang; Huang, Guangxin; Liu, Yu; Guo, Rui (Frontiers in Bioengineering and Biotechnology, 2023)
Traditional non-resorbable bone wax has been used in clinical for more than 100 years. However, the residual bone wax is proven to cause numerous complications. In this study, a novel resorbable bone wax was designed to overcome the disadvantage of traditional non-resorbable bone wax. Alkylene oxide copolymers was used as the main component of resorbable bone wax, additionally, β-tricalcium phosphate and starch microspheres were added to enhance the bone regeneration ability and hemostatic ability. This novel resorbable bone wax has high prospects in clinical translation, and is expected to be developed as a substitute of traditional bone wax.